Fixed exchange rate - a friend or foe of labor cost adjustments? - Lazar Milivojevic; Balint Tatar (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2021)
This paper examines the effectiveness of labor cost reductions as a means to stimulate economic activity and assesses the differences which may occur with the prevailing exchange rate regime. We develop a medium-scale three-region DSGE model and show that the impact of a cut in employers' social security contributions rate does not vary significantly under different exchange rate regimes. We find that both the interest rate and the exchange rate channel matters. Furthermore, the measure appears to be effective even if it comes along with a consumption tax increase to preserve long-term fiscal sustainability. Finally, we assess whether obtained theoretical results hold up empirically by applying the local projection method. Regression results suggest that changes in employers' social security contributions rates have statistically significant real effects - a one percentage point reduction leads to an average cumulative rise in output of around 1.3 percent in the medium term. Moreover, the outcome does not differ significantly across the different exchange rate regimes.
urn:nbn:de:hebis:30:3-564498
Keywords: C53; C54; E32; E37; E61; E62; F41; F45; F47; 330; Structural policies; Labor cost adjustments; Exchange rate regime; Local projection; DSGE